Influence Utilization Waste Plastic Polyethylene Terephthalate on the Flexural Strength of Concrete with Use East Kalimantan Aggregate - Damayanti, Dinda Indah; Indriani, Andi Marini; Utomo, Gunaedy (CIVED, 2023)
Environmental pollution is still an issue that cannot be ignored. This type of waste causes environmental pollution due to its large and difficult to be recycled is Polyethylene Terephthalate (PET) plastic. So it is important to make an effort to utilize the plastic. On the other hand in the world of construction, the use of concrete increases every day causing the need for many new material sources in order to cover the needs of concrete mixtures. One of the abundant sources of aggregate is East Kalimantan aggregate but has not been used much. so combining East Kalimantan aggregate and PET plastic as a concrete constituent material becomes interesting to be analyzed, especially to determine the characteristics of the flexural strength of concrete. The flexural strength is based on SNI 03-4431-2011 method and tested at the age of 14 and 28 days. PET plastic chopped to a size of 5 cm long and 1-3 mm wide with variations 0.5%; 0.65%; and 0.8% of the weight of sand. The total number of samples is 24 blocks size of 15 × 15 × 60 cm. The results indicate that the flexural strength characteristics of concrete using local East Kalimantan aggregates and using PET plastic as a partial substitute for fine aggregate increased as the number of PET substitutions. Concrete without PET plastic has 3.187 MPa. In comparison with to normal concrete, 0.5% PET substitution increased by 3.07%, 0.65% PET variation increased by 3.63% and 0.8% PET variation increased by 4.32%.